Analysis of Legacy System in Software Application Development: A Comparative Survey - M. Srinivas; G. Ramakrishna; K. Rajasekhara Rao; E. Suresh Babu (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Software evolution is one of the challenging issues in today’s business environment. It is necessary for the organizations, which make use of Information, and Communication Technologies will have to align their business processes to compete with global business. The existing large software systems (“legacy” systems) have never been built to cope with the current business requirement for their poor coding, design structures, logic and documentation. Moreover, Legacy applications have various problems such as lack of up to-date documentation, skilled man power, resources of the Legacy applications, and high maintenance costs. Even though the Legacy system is obsolete, it contains detailed business rules and in continuous use, because it satisfies the users' needs and forms the backbone of the information flow of organization. One of the possible solutions is to refactor or modernize those systems into a new platform. It is necessary to analyse the existing legacy system for better understanding the business logic and its functionalities. This paper analyses various techniques proposed for understanding Legacy systems in existence.